2017
DOI: 10.18632/oncotarget.22592
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide enhances doxorubicin-induced apoptosis in prostate cancer cells via activated mitogen-activated protein kinases and generation of reactive oxygen species

Abstract: The management of castration-resistant prostate cancer (CRPC) is challenging, attributable to a lack of efficacious therapies. Chemotherapy is one of the most important treatments for CRPC. Doxorubicin has been extensively used in many different tumors and is often combined with other drugs to enhance effects and reduce toxicity. Costunolide is a natural sesquiterpene lactone with anti-cancer properties. In this study, we first demonstrated that the combination of costunolide and doxorubicin induced apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Reactive oxygen species (ROS) production induced by costunolide may be the important intermediate link of mitochondrial apoptosis. Costunolide has the potential to activate extrinsic pathway or endoplasmic reticulum stress pathway [21][22][23]. Our research group will be further to explore the mechanisms of costunolide via signaling pathway (such as p53, NF-κB and Wnt/β-catenin signaling pathway) and even find the specific molecular target [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) production induced by costunolide may be the important intermediate link of mitochondrial apoptosis. Costunolide has the potential to activate extrinsic pathway or endoplasmic reticulum stress pathway [21][22][23]. Our research group will be further to explore the mechanisms of costunolide via signaling pathway (such as p53, NF-κB and Wnt/β-catenin signaling pathway) and even find the specific molecular target [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The chalcone FKB induces ROS-mediated autophagic cell death (not apoptosis) in AGS cells [27]. Doxorubicin induces ROS-mediated apoptosis in various cancer cells [28,29]. The AGS cells were exposed to various concentrations of FKB 1.5-5 µg/mL and 0.5 µg/mL of doxorubicin for 24 h, respectively, to look into any potential effects as to the propagation and survival of ASG cells.…”
Section: Combination Effects Of Fkb and Doxorubicin On Ags Cellsmentioning
confidence: 99%
“…The chalcone FKB induces (ROS-mediated) autophagy cell death (not apoptosis) in AGS cells [27]. It has also been reported that doxorubicin induces apoptosis in various cancer cells, which is known to be mediated through ROS [28,29]. Therefore, this study was aimed to investigate the synergistic effects of FKB and doxorubicin combination treatment on AGS cells and the role of apoptosis and autophagy mechanisms were elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…While ERK1/2 predominantly operates cell proliferation, JNK and p38 participate in cell death pathways. DOX has been shown to kill prostate cancer cells by phosphorylation of p38 and JNK [74]. One of the MAPKs is p38, which has a pivotal role in cell growth, apoptosis, and inflammation.…”
Section: Apoptotic Cell Death Induced By Doxorubicinmentioning
confidence: 99%